Pendekatan Sosiologis Pada Cerpen “Merdeka” Karya Putu Wijaya - Aini, Dwi Lutfiah; Widyaningtyas, Hanin Mumtazah Putri; Supena, Ahmad (Universitas Pahlawan Tuanku Tambusai, 2025)
This research analyzes Putu Wijaya's short story